Pengaruh Profitabilitas, Leverage, Ukuran Perusahaan, dan Likuiditas Terhadap Nilai Perusahaan - Aprianti, Felicia; Dermawan, Elizabeth Sugiarto (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study was to analyze and obtain empirical evidence regarding the effects of profitability, leverage, firm size,and liquidity on firm value. This research was conducted by using a purposive sampling method with a total sample 153 data from manufacturing companies that listed on the Indonesia Stock Exchange with an observation period of three years, 2018-2020. This research was obtained using secondary data from the financial statements contained on the www.idx.com website. This research was processed using Microsoft Excel and SPSS Statistics version 25. The results obtained from the study concluded that the profitability and firm size variables had a positive and significant effect on firm value, while the leverage and liquidity variables did not have a significant effect on firm value.